Pathomorphology of severe Grade 3-4 hepatic encephalopathy in decompensated cirrhosis patients with acute-on-chronic liver failure - T.V. Shulyatnikova; V.O. Tumanskiy; L.M. Tumanska (Medičnì Perspektivi)
The study was aimed to determine of the most significant pathomorphological signs of severe hepatic encephalopathy (HE) in deceased cirrhotic patients with acute-on-chronic liver failure (ACLF) syndrome based on changes of the glioneuronal complex and the level of tissue ammonia. Using pathohistological, histochemical, and immunohistochemical methods, the cerebral cortex, thalamus, striatum, and cerebellum of 21 deceased patients with acutely decompensated liver cirrhosis with ACLF syndrome and HE Grade 3-4 were examined in comparison with control group, which included 30 deceased patients from acute cardiovascular failure. The study revealed that during HE Grade 3-4 as a component of ACLF, in all studied brain regions, there was a reliably (p<0.05) higher histochemical level of tissue ammonia (up to 500%), increased numbers (up to 215.69%) of apoptotic neurons (according to caspase-3), reduced (up to 119.60%) level of synaptophysin, increased expression of glutamine synthetase (up to 253.02%) and aquaporin-4 (up to 481.81%) associated by reduced (up to 296.81%) expression of glial fibrillary acidic protein in astrocytes, increased (up to 11-fold) numbers of Alzheimer type 2-astrocytes, expansion of perivascular and pericellular «edematous» spaces (up to 890.81%), increased numbers of amyloid bodies (up to 5-fold), increased area of immunopositive material of CD68+ microgliocytes (up to 114.78%) with an increase (up to 71.91%) in the proportion of CD68+ amoeboid microglia. The above-mentioned changes confirm that the loss of consciousness and other psychoneurological manifestations of severe HE Grade 3-4 are due to compound ammonia-associated changes in the components of the glioneuronal complex, namely: adaptive remodeling and dystrophic changes in astrocytes, reduced synaptic transmission and apoptotic neuronal death, reactive changes in microglia with a small proportion of microgliocytes involved in phagocytosis, cytotoxic brain edema and dysfunction of the glymphatic system